PLAGUE AND PESTILENCE IN THE EARLY ISLAMIC LITERATURE VIEWED FROM A CULTURAL RESILIENCE FRAMEWORK: Wabah dalam Puisi Islami: Sebuah Pendekatan Ketahanan Budaya - Muna, Nailil; Nurhamidah, Idha; Idriz, Mesut (Jurnal Lektur Keagamaan, 2022)
ABSTRACT Studies have found that engaging with poetry through poetry reading helps individuals develop positive outlook in life and cope with difficult experience. Poetry has a unique ability to express complex emotions, making it useful for building resilience. This study aims to explore how poetry especially Islamic poetry could serve as a cultural resilience strategy during the pandemic. Cultural resilience refers to the unique way cultural backgrounds such as values, norms, supports, language, and customs can help facilitate an individual or a community to overcome adversity (Clauss-Ehler, 2004). This present study employed reader-response method, involving 21 student-readers who attended Poetry class at Sultan Agung Islamic University, Indonesia. The class was conducted during the Covid-19 pandemic. Three plague-themed Islamic poems were introduced in the poetry reading, such as: The Cholera (1974) by Al-Malaika, The Black Death Plague (1348) by Ibn al-Wardi, and The Night Visitor (c.960) by Al-Mutannabi. This study found that reading poetry positively affected students who have genuine interest in aesthetic reading. The enjoyment in poetry reading could serve as a protective factor for the readers through three major mechanisms: a reminder to the Islamic concept of qadr or preordainment, the consciousness cultivation of pandemics as a shared experience, and the development of empathy out of those experiences. Keywords: Cultural Resilience, Covid-19 Pandemic, Islamic Poetry, Plague, Readers Response. ABSTRAK Studi menunjukkan bahwa penghayatan puisi dapat membantu individu mengembangkan pandangan positif dalam hidup dan mengatasi pengalaman sulit. Puisi memiliki kemampuan unik untuk mengungkapkan emosi yang kompleks, sehingga berguna untuk membangun resiliensi. Studi ini bertujuan untuk mengeksplorasi bagaimana puisi khususnya puisi Islami dapat menjadi strategi ketahanan budaya di masa pandemi. Ketahanan budaya mengacu pada cara unik berlatar belakang budaya seperti nilai, norma, dukungan, bahasa, dan adat istiadat dapat memÂbantu memfasilitasi individu atau komunitas untuk mengatasi kesulitan (Clauss-Ehler, 2004). Penelitian ini menggunakan metode reader-resÂponse, melibatkan 21 mahasiswa-pembaca yang mengikuti kelas Puisi di Universitas Islam Sultan Agung, Indonesia. Kelas diadakan selama pandemi Covid-19. Tiga puisi Islam bertema wabah diperkenalkan dalam pembacaan puisi tersebut, seperti: The Cholera (1974) oleh Al-Malaika, The Black Death Plague (1348) oleh Ibn al-Wardi, dan The Night Visitor (c.960) oleh Al -Mutannabi. Studi ini menemukan bahwa membaca puisi berdampak positif bagi siswa yang memiliki minat dalam membaca esteÂtika. Kenikmatan membaca puisi dapat menjadi faktor pelindung bagi pembacanya melalui tiga mekanisme: pengingat akan konsep Islam tentang qadr atau takdir, penanaman kesadaran akan pandemi sebagai pengalaman bersama, dan pengembangan empati dari pengalaman tersebut. Kata Kunci: Ketahanan Budaya, Pandemi Covid-19, Puisi Islami, Respon Pembaca, Wabah.